Claudins in genitourinary tract neoplasms: mechanisms, prognosis, and therapeutic prospects - Arabi, Tarek Ziad; Ashraf, Nader; Sabbah, Belal Nedal; Ouban, Abderrahman (Frontiers in Cell and Developmental Biology, 2023)
Genitourinary (GU) cancers are among the most prevalent neoplasms in the world, with bladder cancers constituting 3% of global cancer diagnoses. However, several pathogenetic mechanisms remain controversial and unclear. Claudins, for example, have been shown to play a significant role in several cancers of the human body. Their role in GU cancers has not been extensively studied. Aberrant expression of claudins -1, -2, -3, -4, -7, and -11 has been expressed in urothelial cell carcinomas. In prostate cancers, altered levels of claudins -1, -2, -3, -4, and -5 have been reported. Furthermore, the levels of claudins -1, -2, -3, -4, -6, -7, -8, and -10 have been studied in renal cell carcinomas. Specifically, claudins -7 and -8 have proven especially useful in differentiating between chromophobe renal cell carcinomas and oncocytomas. Several of these claudins also correlate with clinicopathologic parameters and prognosis in GU cancers. Although mechanisms underpinning aberrant expression of claudins in GU cancers are unclear, epigenetic changes, tumor necrosis factorɑ, and the p63 protein have been implicated. Claudins also provide therapeutic value through tailored immunotherapy via molecular subtyping and providing therapeutic targets, which have shown positive outcomes in preclinical studies. In this review, we aim to summarize the literature describing aberrant expression of claudins in urothelial, prostatic, and renal cell carcinomas. Then, we describe the mechanisms underlying these changes and the therapeutic value of claudins. Understanding the scope of claudins in GU cancers paves the way for several diagnostic, prognostic, and therapeutic innovations.